2020
DOI: 10.1101/2020.07.22.215962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neonatal hyperoxia enhances age-dependent expression of SARS-CoV-2 receptors in mice

Abstract: The severity of COVID-19 lung disease is higher in the elderly and people with pre-existing co-morbidities. People who were born preterm may be at greater risk for COVID-19 because their early exposure to oxygen at birth increases their risk of being hospitalized when infected with RSV and other respiratory viruses. Our prior studies in mice showed how high levels of oxygen (hyperoxia) between postnatal days 0-4 increases the severity of influenza A virus infections by reducing the number of alveolar epithelia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(76 reference statements)
3
7
0
Order By: Relevance
“…First, the ACE2-positive cells were scattered in the neonatal rat lungs, while they were extensively detected in adult rat lungs (Figure 1), We also found that neonatal pups had fewer AT2 cells (SPC-positive) compared to adult rats (Figure 2), which was consistent with the ACE2 expression in human lungs in other studies [7,18,19]. However, Zhang et al reported ACE2+ cells were extensively stained in lung biopsies from young patients while few were observed in elder patients with COVID-19 [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, the ACE2-positive cells were scattered in the neonatal rat lungs, while they were extensively detected in adult rat lungs (Figure 1), We also found that neonatal pups had fewer AT2 cells (SPC-positive) compared to adult rats (Figure 2), which was consistent with the ACE2 expression in human lungs in other studies [7,18,19]. However, Zhang et al reported ACE2+ cells were extensively stained in lung biopsies from young patients while few were observed in elder patients with COVID-19 [14].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, a particular expression pattern of ACE2 characterized by polarization to the alveolar space was only observed in adults rather than the neonatal lung, which was also demonstrated in adult mice by Yee et al . [19]. Several studies reported that ACE2 protein is low in lung tissue [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model, neonatal hyperoxia increased morbidity from influenza A virus (IAV) ( O'Reilly et al, 2008 ) in a dose-dependent manner ( Maduekwe et al, 2015 ) through pathways involving both alveolar type 2 (AT2) epithelial cells and immune pathways ( Buczynski et al, 2013 ). Furthermore, this effect seems independent of the pathogen, since Yee et al have recently demonstrated that the expression of the SARS-COV2 receptor, ACE2 in club cells, and AT2 cells is increased in adult mice exposed to hyperoxia as neonates ( Yee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by the detection of ACE2 different expression levels in lungs from young and old mice, we extended our analyses to human lung tissue samples by comparing ACE2 immunostaining in histologically normal lung parenchyma of young (20-35 years old) subjects and old (60-80 years old) subjects. ACE2 protein expression levels in the lung parenchyma of old subjects proved to be higher as compared with that of young subjects, as shown and quantified in Fig 1C . Emerging evidence suggests that the severity of SARS-CoV-2 infection correlates with high rates of alveolar epithelial type II (ATII) cells infection (Yee et al, 2020). We took advantage of the single-cell transcriptomic mouse atlas spanning different ages (Almanzar et al, 2020) and focused on the expression data of lungs.…”
Section: Resultsmentioning
confidence: 99%